KEBIJAKAN PEMBAYARAN DALAM PERPAJAKAN - ., Irawati (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2011)
In general, payments and tax deposit is divided into two, namely the payment and remittance of tax payable in a tax period and the payment of taxes payable on the annual tax , contained in Act No. 28 of 2007 KUP. In particular the rules concerning the obligation to make payments for current or withholding tax payment system provided for UU RI no. 36 of 2008 in the Income Tax.